1997
DOI: 10.1172/jci119446
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic peptide inhibitor for alpha-chemokines inhibits the growth of melanoma cell lines.

Abstract: Melanoma growth stimulatory activity (MGSA/GRO ␣ ) is a 73 amino acid peptide sharing sequence characteristics with the ␣ -chemokine superfamily. MGSA/GRO ␣ is produced by diverse melanoma cell lines and reported to act as an autocrine growth factor for the cells. We tested the binding of MGSA/GRO ␣ to melanoma cell lines, Hs 294T and RPMI-7951, and found that these cells could bind to MGSA/GRO ␣ but not to interleukin-8.Recently ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Subsequent work confirmed the ability of CXCL1, CXCL2, and CXCL3 to transform cells and implicated each in angiogenesis [100,101]. Indeed, blockade of chemokine receptor activity with antibodies or a peptide inhibitor was able to decrease tumor growth in vitro and in vivo [102,103]. Similar findings were reported upon neutralization of CXCL1 with the prostate cancer cell line Du145 [104].…”
Section: Cxcl1 Cxcl2 and Cxcl3mentioning
confidence: 61%
“…Subsequent work confirmed the ability of CXCL1, CXCL2, and CXCL3 to transform cells and implicated each in angiogenesis [100,101]. Indeed, blockade of chemokine receptor activity with antibodies or a peptide inhibitor was able to decrease tumor growth in vitro and in vivo [102,103]. Similar findings were reported upon neutralization of CXCL1 with the prostate cancer cell line Du145 [104].…”
Section: Cxcl1 Cxcl2 and Cxcl3mentioning
confidence: 61%
“…Previous studies have shown that antileukinate inhibited the binding of GROa and IL-8 to the receptors on neutrophils , melanoma cells (Hayashi et al 1997), melanocytes (Fujisawa et al 1999a) and endothelial cells (Fujisawa et al 1999b) in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 94%
“…The 125 IGROa was stored at A70°C after the addition of 1% bovine serum albumin (BSA). Recombinant human IL-8 was synthesized and puri®ed as previously described , and was radioactively labeled by the method of Hunter and Greenwood (1962) using chloramine T. Binding studies with adenocarcinoma cell lines were performed as previously described (Hayashi et al 1997). Brie¯y, adenocarcinoma cells were plated in growth medium at a density of 2´10 4 cells/well in a 96-well plate and cultured for 16 h. The cells were then washed twice with Hanks balanced salt solution (HBSS) and incubated with 1 nM radiolabeled GROa or IL-8 and antileukinate (0±500 lg/ml) diluted in 1% BSA at 4°C for 3 h. The incubation was terminated by aspiration of the supernatant.…”
Section: Binding Assaysmentioning
confidence: 99%
“…In addition, overexpression of MGSA/GRO in normal melanocytes leads to anchorage-independent growth in soft agar and tumors in nude mice (Owen et al, 1997). Also, blocking the binding of MGSA/GRO to melanoma cells led to growth inhibition that could be overcome by an excess of MGSA/GRO (Hayashi et al, 1997). Melanomas produce many other growth factors that appear to be important for various aspects of their malignant phenotype (Satyamoorthy and Herlyn, 2002).…”
Section: Growth Factorsmentioning
confidence: 99%